A review of businesses that focus on markets vs. businesses that focus on products in association with market orientation - Christine Reidhead, (Technium Social Sciences Journal, 2020)
A white paper written on building market-focused businesses reported that organizations which are market-focused primarily set their competitive advantage by delivering superior value beneficially to their target customers alongside thriving in their financial performance. However, this conclusion was made only for market-focused businesses, but we believe that the same applies to product-focused businesses in light of the research which can be related to such a strategic approach. In this review, we discuss the two forms of business philosophies; the first is market-focused business philosophy which is primarily concerned with satisfying customers and market needs, and the second, a product-focused business philosophy is concerned with leading through the innovation of the core offerings of an organization. Surprisingly, both these strategic options have so far not been widely explored comparatively in the available literature. Regardless, we propose that both have a relationship with a certain degree of market orientation that can help to solve the mystery regarding which strategic option is superior over another. This relationship further needs to be tested with empirical evidence to help the managers so they can guide the right strategic direction of the company. Furthermore, it is suggested that strategic focus in crisis situations also need to be further analyzed with regard to product-focused and market-focused businesses.